#METOO AND INTERSECTIONALISM: "RADICAL COMMUNITY HEALING" OR "VOYEURISTIC TRAUMA PORN?" - Trott, Verity (AoIR Selected Papers of Internet Research, 2019)
In October 2017, millions of people reflected on their experiences of sexual abuse and harassment, publicly sharing their testimonials in an expression of global vulnerability using the hashtag #MeToo. Many of the tweets portrayed the angst and distress individuals experienced in their decision to participate, indicating the psychological costs of engaging with #MeToo. Further, some tweets expressed frustration at the re-appropriated nature of the campaign and the collective feeling of an “intersectional betrayal” by white women and feminists who dominated the mainstream media reporting of the movement. This research foregrounds the intersectional concerns that result from the scale and reach of the millions of testimonials suspended online that constitute the #MeToo movement. It highlights how the many stories that have circulated the online sphere obscure the absence and recognition of marginalised women and those who are already more vulnerable in regards to experiencing sexual assault. The paper adopts an intersectional framework, as conceptualised by Crenshaw (1991), to further an understanding of how race, class, and gender collide and how subordination can be reproduced within feminist protests. Drawing on a large data set of tweets, this research combines content, discourse and social network analysis to examine the narratives related to participation. The paper highlights the experiences and reflections of users who self-identified as queer, disabled, or a person of colour within their tweets. A social network analysis is also used to visualise a snapshot of the affective publics that arose at the beginning and to illustrate how systems of oppression converge.